2021
DOI: 10.3389/fmed.2021.652707
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width Upon Hospital Admission Predicts Short-Term Mortality in Hospitalized Patients With COVID-19: A Single-Center Experience

Abstract: Background: Coronavirus disease (COVID-19) was first described at the end of 2019 in China and has since spread across the globe. Red cell distribution width (RDW) is a potent prognostic marker in several medical conditions and has recently been suggested to be of prognostic value in COVID-19.Methods: This retrospective, observational study of consecutive patients with COVID-19 was conducted from March 12, 2020 to December 4, 2020 in the Wilhelminenhospital, Vienna, Austria. RDWlevels on admission were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…RDW reflects the heterogeneity of erythrocyte volume and assess the variation in size and form of circulating erythrocytes. The increase in RDW reflects the increase in other inflammatory markers in the blood (16). Cytokines may directly inhibit erythropoietin-induced erythrocyte maturation which leads to an increase in RDW (17).…”
Section: �Correlation Between Mean Platelet Volume and Other Laborato...mentioning
confidence: 99%
“…RDW reflects the heterogeneity of erythrocyte volume and assess the variation in size and form of circulating erythrocytes. The increase in RDW reflects the increase in other inflammatory markers in the blood (16). Cytokines may directly inhibit erythropoietin-induced erythrocyte maturation which leads to an increase in RDW (17).…”
Section: �Correlation Between Mean Platelet Volume and Other Laborato...mentioning
confidence: 99%
“…25 studies 33–57 out of 1,008 identified publications were incorporated according to the inclusion criteria (Figure 1; Table 1). 19 articles were peer‐reviewed and 6 were preprints 35–37,40,45,53 .…”
Section: Resultsmentioning
confidence: 99%
“…There were several studies that defined ≥14.5% as the abnormally elevated RDW, and have demonstrated good predictive performance in terms of unfavorable clinical outcomes. 15 , 16 , 17 , 18 However, some studies found that cutoff values from different centers might vary—ranging from 12.85% to 14.35%. 19 , 20 , 21 , 22 The cutoff value generated in our study population was 11.5%, which was close to Wang et al 21 Whether the minor difference between the cutoff values of our study and Wang et al's study was significant required further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there was no consensus on the optimal cutoff of RDW. There were several studies that defined ≥14.5% as the abnormally elevated RDW, and have demonstrated good predictive performance in terms of unfavorable clinical outcomes 15–18 . However, some studies found that cutoff values from different centers might vary—ranging from 12.85% to 14.35% 19–22 .…”
Section: Discussionmentioning
confidence: 99%